Effect of Excess Iodide Intake on Salivary Glands in a Swiss Albino Mice Model - Ross, Gloria Romina (2017)
Iodine is an important micronutrient required for nutrition. Excess iodine has adverse effects on thyroid, but there is not enough information regarding its effect on salivary glands. In addition to food and iodized salt, skin disinfectants and maternal nutritional supplements contain iodide, so its intake could be excessive during pregnancy, lactation, and infancy. The aim of this work was to evaluate the effect of excess iodide ingestion on salivary glands during mating, gestation, lactation, and postweaning period in mouse. During assay, mice were allocated into groups: control and treatment groups (received distilled water with NaI 1 mg/mL). Water intake, glandular weight, and histology were analyzed. Treatment groups showed an increase in glandular weight and a significantly (p < 0.05) higher water intake than control groups. Lymphocyte infiltration was observed in animals of treatment groups, while there was no infiltration in glandular sections of control groups. Results demonstrated that a negative relationship could exist between iodide excess and salivary glands. This work is novel evidence that high levels of iodide intake could induce mononuclear infiltration in salivary glands. These results should be considered, especially in pregnant/lactating women, to whom a higher iodine intake is usually recommended.